Antiviral Peptides Delivered by Chitosan-Based Nanoparticles to Neutralize SARS-CoV-2 and HCoV-OC43 - Avinash Mali; Gianluigi Franci; Carla Zannella; Annalisa Chianese; Shubaash Anthiya; Ana M. López-Estévez; Alessandra Monti; Anna De Filippis; Nunzianna Doti; María José Alonso; Massimiliano Galdiero (MDPI AG, 2023)
The COVID-19 pandemic has made it clear that there is a crucial need for the design and development of antiviral agents that can efficiently reduce the fatality rate caused by infectious diseases. The fact that coronavirus mainly enters through the nasal epithelial cells and spreads through the nasal passage makes the nasal delivery of antiviral agents a promising strategy not only to reduce viral infection but also its transmission. Peptides are emerging as powerful candidates for antiviral treatments, showing not only a strong antiviral activity, but also improved safety, efficacy, and higher specificity against viral pathogens. Based on our previous experience on the use of chitosan-based nanoparticles to deliver peptides intra-nasally the current study aimed to explore the delivery of two-novel antiviral peptides making use of nanoparticles consisting of HA/CS and DS/CS. The antiviral peptides were chemically synthesized, and the optimal conditions for encapsulating them were selected through a combination of physical entrapment and chemical conjugation using HA/CS and DS/CS nanocomplexes. Finally, we evaluated the in vitro neutralization capacity against SARS-CoV-2 and HCoV-OC43 for potential use as prophylaxis or therapy.